A general integration scheme in quadrature element method. (July 2020) - Wang, Xinwei; Yuan, Zhangxian; Jin, Chunhua
Abstract: For the first time, a general integration scheme is proposed which can be employed in the development of quadrature elements with nodes of any type. With the proposed scheme, explicit formulations of quadrature elements with an arbitrary number of nodes can be derived indirectly via the differential quadrature law. Similar to the conventional finite element method, either reduced or full integration can be adopted in the explicit formulation by using the proposed scheme.